Immunotherapy of Childhood Sarcomas - Roberts, Stephen S.; Chou, Alexander J.; Cheung, Nai-Kong V. (Frontiers in Oncology, 2015)
Pediatric sarcomas are a heterogeneous group of malignant tumors of bone and soft tissue origin. Although more than 100 different histologic subtypes have been described, the majority of pediatric cases belong to the Ewing’s family of tumors, rhabdomyosarcoma and osteosarcoma. Most patients that present with localized stage are curable with surgery and/or chemotherapy; however, those with metastatic disease at diagnosis or those who experience a relapse continue to have a very poor prognosis. New therapies for these patients are urgently needed. Immunotherapy is an established treatment modality for both liquid and solid tumors, and in pediatrics, most notably for neuroblastoma and osteosarcoma. In the past, immunomodulatory agents such as interferon, interleukin-2, and Liposomal-muramyl  tripeptide phosphatidyl-ethanolamine (L-MTP) have been tried, with some activity seen in subsets of patients; additionally, various cancer vaccines have been studied with possible benefit. Monoclonal antibody therapies against tumor antigens such as disialoganglioside GD2 or immune checkpoint targets such as CTLA4 and PD-1 are being actively explored in pediatric sarcomas. Building on the success of adoptive T cell therapy for EBV-related lymphoma, strategies to redirect T cells using chimeric antigen receptors and bispecific antibodies are rapidly evolving with potential for the treatment of sarcomas. This review will focus on recent preclinical and clinical developments in targeted agents for pediatric sarcomas with emphasis on the immunobiology of immune checkpoints, immunoediting, tumor microenvironment, antibody engineering, cell engineering, and tumor vaccines. The future integration of antibody based and cell based therapies into an overall treatment strategy of sarcoma will be discussed.